A Reexamination of the Conglomerate Merger Wave in the 1960s: An Internal Capital Markets View - Hubbard, R. Glenn; Palia, Darius (Journal of Finance, 1999)
One possible explanation for bidding firms earning positive abnormal returns in diversifying acquisitions in the 1960s is that internal capital markets were expected to overcome the information deficiencies of the less‐developed capital markets. Examining 392 bidder firms during the 1960s, we find the highest bidder returns when financially “unconstrained” buyers acquire “constrained” targets. This result holds while controlling for merger terms and for different proxies used to classify firms facing costly external financing. We also find that bidders generally retain target management, suggesting that management may have provided company‐specific operational information, while the bidder provided capital‐budgeting expertise.